Preparation method of hierarchical pore size material based on diatomite
By combining calcination and wet dry mixing, multi-stage pore size diatomaceous earth material is prepared, which solves the problem that the diatomaceous earth micropores cannot fully exert its humidity regulation performance in the prior art, and realizes the lightweight and efficient absorption/discharging effect of the material.
Patent Information
- Application Number
- CN202510061499.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
After the prior art, diatomaceous earth is incorporated into other materials, it is unable to fully exert its micropore humidity regulating properties, resulting in the material being not light enough and the absorption/discharging rate is insufficient.
The organic matter in diatomaceous earth was removed by calcination treatment, and dry-mixed with calcium oxide, fume and calcium stearate and stirred based on water. Then add aerated aluminum paste for high-speed stirring and foaming. Finally, pre-curing and autoclaving under constant temperature and humidity conditions were performed to prepare lightweight materials with multi-stage pore sizes.
It realizes the lightweight material and the efficient use of microporous advantages, improves the absorption/discharging rate, and enhances the overall performance of the material.
Smart Images

Figure HDA0005243019540000011
Abstract
Description
Technical Field
[0001] The invention relates to the field of porous materials, in particular to a method for preparing a multi-level pore size material based on diatomite. Background Art
[0002] Diatomaceous earth is a biological siliceous sedimentary rock formed by the deposition of the siliceous remains of diatoms and other microorganisms. It has abundant global reserves and is widely distributed. Its main chemical component is amorphous silicon dioxide, which has certain volcanic ash activity. Due to its natural porous structure and characteristics, diatomaceous earth has the characteristics of adsorption, heat insulation, sound absorption, humidity control, etc., so it is widely used in building materials.
[0003] The Chinese invention with application number 202011431766.7 discloses a method for preparing foamed, lightweight, and high-temperature resistant diatomite insulation bricks. First, the organic impurities in the diatomite are removed, and the diatomite is heat-set at high temperature. Then, the diatomite powder, high-alumina cement, and high-temperature auxiliary materials are mixed into a water foaming system using an automatic production line to make a foam slurry. The lightweight and high-temperature resistant diatomite insulation bricks are cast and hardened into shape in a short time. The bricks are demolded, moved, and stacked immediately, and dried and shaped for shipment in a short time.
[0004] The Chinese invention with application number 202210375744.6 discloses a diatomaceous earth-activated porous lightweight concrete and its preparation method and use. The concrete is mixed with the following raw materials by weight: 15 to 25 parts of sodium silicate, 30 to 70 parts of correction materials, and 10 to 14 parts of diatomaceous earth; the concrete density is 800 to 900 kg / m 3 . Effectively utilize the abundant diatom resources in the ocean, use alkali to stimulate them into cementitious materials, and then further add admixtures, chemical foaming agents, etc. to prepare porous lightweight concrete.
[0005] However, most current studies use diatomaceous earth as an admixture and directly add it to materials such as cement. The materials prepared in this way are not only not light enough, but also cause the diatomaceous earth to be unable to contact the surrounding environment well, thus resulting in its microporous humidity regulating performance not being able to be fully utilized. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a multi-level pore material based on diatomite, overcome the shortcomings of the prior art, solve the problem that after diatomite is added to other materials under conventional methods, its microporous advantages cannot be brought into play, improve the material's own moisture adsorption, humidity control, and lightweight properties, and obtain a greater moisture absorption / desorption rate.
[0007] In order to achieve the above technical objectives, the present invention is implemented through the following technical solutions:
[0008] A method for preparing a multi-level pore size material based on diatomite comprises the following steps:
[0009] 1) calcining the diatomaceous earth to fully remove its organic matter;
[0010] 2) The calcined diatomaceous earth from step 1) is put into a mixer according to a certain proportion with calcium oxide, silica fume and calcium stearate, and dry mixed for 10-30 minutes. Then the mixed materials are put into a blender, and water is added and stirred to form a paste:
[0011] 3) Add the formulated amount of gas-forming aluminum paste to the paste prepared in step 2), stir at high speed for 30 seconds, and then immediately pour into the concrete test mold and let it stand for foaming:
[0012] 4) After the foaming in step 3) is completed, the entire test mold is placed in a constant temperature and humidity curing box for pre-curing;
[0013] 5) After the pre-curing in step 4), the sample is demoulded and placed in a cement autoclave for autoclave curing. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore size material.
[0014] Furthermore, the SiO2 content of the diatomite in step 1) before calcination is 56.02%, and the specific surface area is 55.59 m2 / g; after calcination, the SiO2 content is 67.26%, the specific surface area is 60.30 m2 / g, and the organic impurity content is less than 11.24%.
[0015] Furthermore, the calcination temperature in step 1) is 500-550° C., and the calcination time is 2-6 hours.
[0016] Furthermore, in the step 2), the weight ratio of water to diatomaceous earth is 1:1.
[0017] Furthermore, the mixing ratio of the components in step 2) is: 240-300 parts of diatomaceous earth, 60-80 parts of calcium oxide, and 20-40 parts of silica fume.
[0018] Furthermore, the components also include, by weight, 0.5-2.0 parts of calcium stearate.
[0019] Furthermore, in step 3), 0.2-2.0 parts of aerated aluminum paste is used, and the aerated aluminum paste is commercially available GLS-65 aluminum powder paste for aerated bricks.
[0020] Furthermore, in step 3), the mixer is a cement mortar mixer, and the mixing speed is 50-120 rpm.
[0021] Furthermore, the pre-curing conditions in step 4) are: humidity is 90%, temperature is 50-70° C., and pre-curing time is 3-6 hours.
[0022] Furthermore, the steam curing conditions in step 5) are: 180-220° C., steam pressure 1-2 MPa, and time 5-10 h.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1) After adding gas-generating aluminum paste in an alkaline environment, the reaction generates gas, and the gas is trapped in the material as it solidifies. The multi-pore structure finally formed not only provides a skeleton and overall porosity for the material, but also allows diatomaceous earth particles to be evenly distributed on the pore walls or inside the pores of the foamed cement macropores, thereby obtaining a uniform multi-level pore lightweight material;
[0025] 2) It enhances the interaction between the micropores of diatomite and the external environment. By constructing a multi-level pore structure with synergistic effects between micropores and macro-control, the micropore advantages of diatomite can be more efficiently exerted with the support of gas-generating aluminum paste. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A macroscopic-microscopic picture of the multi-level aperture material provided by the present invention;
[0027] In the figure: (a) is the original camera photo of the foam material, (b) is the cross-sectional photo of the foam material after being magnified 40 times under a high-definition CCD microscope, (c) is the cross-sectional photo of the foam material after being magnified 300 times under a scanning electron microscope, and (d) is the cross-sectional photo of the foam material after being magnified 2000 times under a scanning electron microscope. DETAILED DESCRIPTION
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the specific embodiments required to be used in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the specific embodiments described below are some implementation methods of the present invention. For ordinary technicians in this field, other specific embodiments can be obtained based on these specific embodiments without paying creative work.
[0030] The components of the embodiments of the present invention generally described and shown in the specific embodiments herein can be arranged and designed in countless different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the specific embodiments is not intended to limit the scope of the invention claimed, but merely represents selected embodiments of the present invention.
[0031] In the following Examples 1-9, the SiO2 content of the diatomite used before calcination was 56.02% and the specific surface area was 55.59 m 2 / g; after calcination, the SiO2 content is 67.26% and the specific surface area is 60.30m 2 / g. The gas-generating aluminum paste used is the commercially available GLS-65 aluminum powder paste for aerated bricks. The mixer is a cement mortar mixer with a stirring speed of 50-120 rpm. The calcium oxide and calcium stearate used are both chemically pure preparations. The content of SiO2 in silica fume is not less than 90%. The concrete test mold specification is 70mm×70mm×70mm.
[0032] The dry density and compressive strength of the obtained foamed material were tested according to the "Test Methods for Inorganic Rigid Thermal Insulation Products" (GB / T5486-2008). The humidity control performance was tested according to the "Test Methods for Moisture Absorption and Desorption Performance of Building Materials" (JC / T 2002-2009).
[0033] Example 1
[0034] The method for preparing a multi-level pore material based on diatomite in Example 1 comprises the following steps:
[0035] (1) calcining diatomite at a temperature of 500° C. for 2 h;
[0036] (2) Take 240 parts of calcined diatomaceous earth, 60 parts of calcium oxide, 40 parts of silica fume, and 0.5 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 240 parts of water, and continue to stir until a uniform paste is formed;
[0037] (3) adding 0.2 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0038] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 50° C. for pre-curing for 3 hours;
[0039] (5) After the pre-curing in step (4), the sample is demoulded and placed in a cement autoclave for autoclave curing at 183° C. and 1 MPa for 5 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore material based on diatomite.
[0040] The dry density of the foamed material obtained in Example 1 is 892 kg / m 3 , the compressive strength is 6.71MPa, and the maximum moisture absorption / desorption rate is 10.11% / 4.85%.
[0041] Example 2
[0042] A method for preparing a multi-level pore size material based on diatomite in Example 2 comprises the following steps:
[0043] (1) Same as Example 1;
[0044] (2) Take 260 parts of calcined diatomaceous earth, 70 parts of calcium oxide, 30 parts of silica fume, and 0.7 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 260 parts of water, and continue to stir until a uniform paste is formed;
[0045] (3) adding 0.2 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0046] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 70° C. for pre-curing for 4 hours;
[0047] (5) After the pre-curing in step (4), the sample is demolded and placed in a cement autoclave for autoclave curing at 187° C. and 1.1 MPa for 6 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore material based on diatomite.
[0048] The dry density of the foamed material obtained in Example 2 is 889 kg / m 3 , the compressive strength is 6.73MPa, and the maximum moisture absorption / desorption rate is 9.91% / 4.54%.
[0049] Example 3
[0050] A method for preparing a multi-level pore size material based on diatomite in Example 3 comprises the following steps:
[0051] (1) Same as Example 1;
[0052] (2) Take 280 parts of calcined diatomaceous earth, 80 parts of calcium oxide, 20 parts of silica fume, and 0.9 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 280 parts of water, and continue to stir until a uniform paste is formed;
[0053] (3) adding 0.2 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0054] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 60° C. for pre-curing for 5 hours;
[0055] (5) After the pre-curing in step (4), the sample is demoulded and placed in a cement autoclave for autoclave curing at 192° C. and 1.2 MPa for 6 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore size foam material.
[0056] The dry density of the foamed material obtained in Example 3 is 887 kg / m 3 , the compressive strength is 6.69MPa, and the maximum moisture absorption / desorption rate is 10.12% / 4.59%.
[0057] Example 4
[0058] The method for preparing a multi-level pore material based on diatomite in Example 4 comprises the following steps:
[0059] (1) Same as Example 1;
[0060] (2) Take 250 parts of calcined diatomaceous earth, 60 parts of calcium oxide, 30 parts of silica fume, and 0.7 parts of calcium stearate, dry mix them in a mixer for 10 minutes, then pour them into a cement mortar mixer, add 250 parts of water, and continue stirring until a uniform paste is formed;
[0061] (3) adding 0.3 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0062] (4) After the foaming in step (3) is completed, the entire test mold is placed in a 50°C constant temperature and humidity curing box for pre-curing for 6 hours; (5) After the pre-curing in step (4) is completed, the sample is demolded and placed in a cement autoclave for autoclave curing. The curing conditions are 183°C 1MPa 6 hours. After the curing is completed, the material is naturally cooled to room temperature to obtain a multi-level pore material based on diatomite.
[0063] The dry density of the foamed material obtained in Example 4 is 884 kg / m 3 , compressive strength is 6.65MPa, and the maximum moisture absorption / desorption rate is 10.67% / 4.39%.
[0064] Example 5
[0065] A method for preparing a multi-level pore size material based on diatomite in Example 5 comprises the following steps:
[0066] (1) Same as Example 1;
[0067] (2) Take 300 parts of calcined diatomaceous earth, 80 parts of calcium oxide, 30 parts of silica fume, and 0.5 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 300 parts of water, and continue stirring until a uniform paste is formed;
[0068] (3) adding 0.3 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0069] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 50° C. for pre-curing for 4 hours;
[0070] (5) After the pre-curing in step (4), the sample is demolded and placed in a cement autoclave for autoclave curing at 183° C. and 1 MPa for 7 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore material based on diatomite.
[0071] The dry density of the foamed material obtained in Example 5 is 880 kg / m 3 , the compressive strength is 6.58MPa, and the maximum moisture absorption / desorption rate is 10.52% / 4.84%.
[0072] Example 6
[0073] A method for preparing a multi-level pore material based on diatomite in Example 6 comprises the following steps:
[0074] (1) Same as Example 1;
[0075] (2) Take 270 parts of calcined diatomaceous earth, 70 parts of calcium oxide, 35 parts of silica fume, and 0.9 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 270 parts of water, and continue to stir until a uniform paste is formed;
[0076] (3) adding 0.2 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0077] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 60° C. for pre-curing for 4 hours;
[0078] (5) After the pre-curing in step (4), the sample is demoulded and placed in a cement autoclave for autoclave curing at 183° C. and 1 MPa for 5 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore foam material.
[0079] The dry density of the foamed material obtained in Example 6 is 893 kg / m 3 , the compressive strength is 6.67MPa, and the maximum moisture absorption / desorption rate is 10.46% / 4.71%.
[0080] Example 7
[0081] A method for preparing a multi-level pore size material based on diatomite in Example 7 comprises the following steps:
[0082] (1) Same as Example 1;
[0083] (2) Take 240 parts of calcined diatomaceous earth, 80 parts of calcium oxide, 40 parts of silica fume, and 0.7 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 240 parts of water, and continue to stir until a uniform paste is formed;
[0084] (3) adding 0.2 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0085] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 60° C. for pre-curing for 3 hours;
[0086] (5) After the pre-curing in step (4), the sample is demolded and placed in a cement autoclave for autoclave curing at 187° C. and 1.1 MPa for 5 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore material based on diatomite.
[0087] The dry density of the foamed material obtained in Example 7 is 890 kg / m 3 , the compressive strength is 6.70MPa, and the maximum moisture absorption / desorption rate is 10.79% / 4.91%.
[0088] Example 8
[0089] A method for preparing a multi-level pore material based on diatomite in Example 8 comprises the following steps:
[0090] (1) Same as Example 1;
[0091] (2) Take 270 parts of calcined diatomaceous earth, 60 parts of calcium oxide, 40 parts of silica fume, and 0.7 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 270 parts of water, and continue to stir until a uniform paste is formed;
[0092] (3) adding 0.3 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0093] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 70° C. for pre-curing for 3 hours;
[0094] (5) After the pre-curing in step (4), the sample is demolded and placed in a cement autoclave for autoclave curing at 187° C. and 1.1 MPa for 6 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore material based on diatomite.
[0095] The dry density of the foamed material obtained in Example 8 is 886 kg / m 3, the compressive strength is 6.62MPa, and the maximum moisture absorption / desorption rate is 11.14% / 5.22%.
[0096] Example 9
[0097] A method for preparing a multi-level pore size material based on diatomite in Example 9 comprises the following steps:
[0098] (1) Same as Example 1;
[0099] (2) Take 300 parts of calcined diatomaceous earth, 70 parts of calcium oxide, 40 parts of silica fume, and 0.7 parts of calcium stearate, dry mix them in a mixer for 10 minutes, pour them into a cement mortar mixer, add 300 parts of water, and continue to stir until a uniform paste is formed;
[0100] (3) adding 0.3 parts of gas-forming aluminum paste to the paste prepared in step (2) and stirring at high speed for 30 seconds, and then immediately pouring it into a concrete test mold and letting it stand for foaming;
[0101] (4) After the foaming in step (3) is completed, the entire test mold is placed in a constant temperature and humidity curing box at 50° C. for pre-curing for 5 hours;
[0102] (5) After the pre-curing in step (4), the sample is demolded and placed in a cement autoclave for autoclave curing at 187° C. and 1.1 MPa for 7 h. After the curing, the sample is naturally cooled to room temperature to obtain a multi-level pore material based on diatomite.
[0103] The dry density of the foamed material obtained in Example 9 is 877 kg / m 3 , the compressive strength is 6.56MPa, and the maximum moisture absorption / desorption rate is 10.96% / 5.01%.
[0104] See Figure 1 , which is a macroscopic-microscopic picture of the multi-level aperture material provided by the present invention, from Figure 1 It can be seen that the macropores prepared by foaming the gas-generating aluminum paste and the micropores of the diatomite particles distributed on the pore walls or inside the pores of these macropores form a multi-level pore structure. While achieving the lightweight of the material, it also enhances the interaction between the diatomite micropores and the external environment. By constructing a multi-level pore structure with synergistic effects between micropores and macropores, the micropore advantages of diatomite can be more efficiently exerted with the support of these pores.
[0105] Comparative Example
[0106] The mixing proportions of the components by weight are: 60 parts of diatomaceous earth, 16 parts of quicklime, 8 parts of cement, 9 parts of wollastonite, 4 parts of gypsum, 2 parts of wood fiber, and 1 part of glass fiber.
[0107] The specific implementation steps are as follows: a) weighing each component according to the above weight proportion; b) stirring the raw materials taken in step a with a mixer for 30min-50min to fully mix and obtain a mixture; c) adding water accounting for 0.5 times the weight of the mixture in step b and stirring for another 10min to make the mixture into a slurry; d) then adopting a slurry flow method to make a blank, pouring the slurry in step c into a mold and using a pressure of 200kN-500kN for dehydration molding, demolding after 1min, and controlling the moisture content of the blank to be 35%-40%; e) drying the blank obtained in step d at 50-105℃ for 1h-4h, and then curing it at 10-11 atmospheres and 193℃-210℃ for 6h-12h, and finally obtaining a diatomite board product with humidity control function.
[0108] The dry density of the foamed material obtained in the comparative example is 1050 kg / m 3 , the compressive strength is 5.42MPa, the moisture absorption rate is 4.41%, and the moisture release rate is 1.3%.
[0109] It should be noted that the above implementation methods are only used to illustrate the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the embodiments, it should be understood by those skilled in the art that various combinations, modifications or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a multi-level pore size material based on diatomite, characterized in that: The following steps are involved: 1) calcining the diatomaceous earth to fully remove its organic matter; 2) The calcined diatomaceous earth from step 1) is put into a mixer according to a certain proportion with calcium oxide, silica fume and calcium stearate, and dry mixed for 10-30 minutes. Then the mixed materials are put into a blender, and water is added and stirred to form a paste: 3) Add the formulated amount of gas-forming aluminum paste to the paste prepared in step 2), stir at high speed for 30 seconds, and then immediately pour into the concrete test mold and let it stand for foaming: 4) After the foaming in step 3) is completed, the entire test mold is placed in a constant temperature and humidity curing box for pre-curing; 5) After the pre-curing in step 4), the sample is demoulded and placed in a cement autoclave for autoclave curing. After the curing, the sample is naturally cooled to room temperature to obtain a graded pore size material.
2. The method for preparing a multi-level pore size material based on diatomite according to claim 1, characterized in that: The SiO2 content of the diatomite in step 1) before calcination is 56.02%, and the specific surface area is 55.59 m 2 / g; after calcination, the SiO2 content is 67.26% and the specific surface area is 60.30m 2 / g, and the organic impurity content is less than 11.24%.
3. The method for preparing a multi-level pore material based on diatomite according to claim 1, characterized in that: The calcination temperature in step 1) is 500-550° C., and the calcination time is 2-6 hours.
4. The method for preparing a multi-level pore size material based on diatomite according to claim 1, characterized in that: The weight ratio of water to diatomaceous earth in step 2) is 1:
1.
5. The method for preparing a multi-level pore size material based on diatomite according to claim 1, characterized in that: The mixing ratio of the components in step 2) is: 240-300 parts of diatomaceous earth, 60-80 parts of calcium oxide, and 20-40 parts of silica fume.
6. The method for preparing a multi-level pore size material based on diatomite according to claim 5, characterized in that: The components further include, by weight, 0.5-2.0 parts of calcium stearate.
7. The method for preparing a multi-level pore size material based on diatomite according to claim 1, characterized in that: In the step 3), 0.2-2.0 parts of aerated aluminum paste is used, and the aerated aluminum paste is commercially available GLS-65 aluminum powder paste for aerated bricks.
8. The method for preparing a multi-level pore size material based on diatomite according to claim 1, characterized in that: In the step 3), the mixer is a cement mortar mixer, and the mixing speed is 50-120 rpm.
9. The method for preparing a multi-level pore size material based on diatomite according to claim 1, characterized in that: The pre-curing conditions in step 4) are: humidity of 90%, temperature of 50-70° C., and pre-curing time of 3-6 hours.
10. The method for preparing a multi-level pore size material based on diatomite according to claim 1, characterized in that: The steam curing conditions in step 5) are: 180-220° C., steam pressure 1-2 MPa, and time 5-10 h.
Citation Information
Patent Citations
Preparation method of foamed light high-temperature-resistant diatomite insulating brick
CN112500190A
A diatomaceous earth-induced alkali-activated porous lightweight concrete for deep-sea floating island construction, its preparation method and applications.
CN114685104B